A Comprehensive Literature Review on The Applications of Pattern Recognition with A Focus on Biometrics - D. Vasu babu (AG Volumes, 2022)
Pattern recognition concerns with detecting a pattern and verifying it again. In general, a pattern may be a handwritten cursive word, a fingerprint picture, a human face, a bar code, a voice signal, or a web page on Internet. The distinct designs are generally categorized into numerous groups depending on their features. When the patterns with identical qualities are put together, the resulting group is itself a pattern, that is commonly termed a pattern class. Pattern recognition is the science for detecting, recognizing the patterns of interest, then making right judgements about patterns or the pattern classes. Thus, a biometric system employs pattern recognition to identify as well as categorise the persons, by comparing it with the recorded template. In this paper, an attempt has been made to present a comprehensive review on the applications of pattern recognition techniques in different fields with a special focus on the biometrics.